Effect of Overburden Depth and Stress Anisotropy on a Ground Reaction Caused by Advancing Excavation of a Circular Tunnel - Yu-Lin Lee; Ming-Long Zhu; Chi-Huang Ma; Chih-Sheng Chen; Chi-Min Lee (Mathematics, 2023)
The assumption of the Convergence–Confinement Method (CCM) is the analysis of the interaction behavior of the support and ground of a deep circular tunnel under an isotropic stress field. Aiming to improve this method, this paper proposes a discussion on the influence of the overburden depth and stress anisotropy. To consider the influence of the overburden effect, the ground reaction in different depths due to tunnel advancing excavation is investigated. Under anisotropic stress conditions, the analytical solutions of the stress/displacement in the plastic and elastic regions of this ground reaction can also be suitable for theoretical analysis in a consistent manner. The key factor in this study is the use of confinement loss, which can not only describe the simulation of tunnel advancing effects but also become a superimposed value of the incremental procedure. In addition, the calculation spreadsheets can be used to estimate and implement the theoretical analytical solutions into executable computational solutions. To check the validity of the analytical solution, finite element analysis is used to examine the distribution of stress/displacement around the tunnel, especially the distribution along the overburden pressure line in the circular tunnel cross-section. Comparing the analytical solution calculated by the incremental procedure with the result of the numerical analysis shows a consistent trend.